Paciente femenino de 19 años de edad presenta problemas visuales a causa de insuficiencia de convergencia. - Laman Moran, Daniela Alejandra (2021)
The clinical case is going to be about a 19-year-old female patient who presents visual problems due to convergence insufficiency. Convergence insufficiency is a common disease related to the coordination of the eye muscles, in which the eyes cannot function together when looking at close objects. This disorder causes one eye to move outward rather than inward along with the other eye, causing blurred or double vision. The objective of the research is to determine the effects of this convergence insufficiency problem in a 19-year-old patient. The applied methodology is based on the meticulous analysis of the clinical case, anamnesis, family history, family pathological history, physical examinations such as: retinoscopy (RX), fundus, biomicroscopy, author refractometer (AR), near point of convergence (PPC), distance visual acuity (AVL), near visual acuity (AVC), visual acuity with correction (AVCC), ocular motility and other complementary tests that are of utmost importance to establish an adequate optometric treatment. The results obtained in this research process were the following: especially the symptoms: eye fatigue, asthenopia, headaches (especially frontal), blurred vision, diplopia in near vision and difficulty in concentrating on a fixed point, or in reading. The treatment established for this problem is as follows: .-Push-up: bring a pencil to the midline of the eyes trying to maintain the fusion (series of 20 to 30 repetitions).- Brock's cord: A rope of between 1.5 and 3 meters is used with a number of balls between 2 and 6 with a diameter of 0.31 to 2.54 cm of different colors. One end of the Brock's cord is placed on the nose and the other with a nail attached to the wall, the patient is asked to observe the 1st ball of the cord as sharp and unique while the back ones are perceived as double and vice versa.- Optical correction using positive lenses of (BE: +0.25 ESF). The conclusion of this work was the progress in eliminating headache and eye pain fatigue, in addition to establishing a better optimal vision, which by means of the aforementioned treatment would be coordinated in relation to the ocular muscles.